Rethinking Inclusion: English Language Teachers’ Representations Towards Functionally Diverse Students - Barrero Rico, Cristhian Camilo (Colombian Applied Linguistics Journal, 2025)
This article challenges the discourses and practices embedded in inclusive education in Colombia as enacted in policies and biological, social, and moral models of human rights. Drawing on critical disability theory, it unsettles the domesticated conceptualization of disability(ies) provided by inclusive teaching policies and deficitarian human rights-based models. This pedagogical stance enables the exploration of English language (EL) teachers’ representations of functionally diverse (FD) students in inclusive settings. The article grapples with contradictions in the educational system that render inclusionary practices, structure, terminologies stemmed from a pathologizing education of the FD children. These contradictions generate representational tensions, meanings, and implications for the teaching of English as a foreign language. The data collection instruments were semi-structured interviews, written narratives, and official texts. The findings suggest that EL teachers normalize and denaturalize inclusive discourses and deficit views derived from inclusive education. The study concludes that EL teachers resist and transform institutionalized inclusive practices through a pedagogical self-discovery, that is a EL personal discursive construction(s) situated within their views of inclusive education.